Work-related upper limb amputations in Taiwan, 1999-2001 - Liang, Huey-Wen; Chen, Ssu-Yuan; Hsu, Jin-Huei; Chang, Chein-Wei (American journal of industrial medicine, 2004)
Background Work‐related upper limb amputations account for a significant number of occupational injuries. This study analyzes the nationwide incidence of work‐related amputations of upper limbs in Taiwan by using the workers' compensation database. Methods A total of 2,950 cases were retrieved and analyzed from the database of workers' compensatory disability claims between the years 1999 and 2001. Results The cases were workers with an average age of 39.1 years, of whom 23.0% were female, the highest percentage of cases was in the 30–49 age group, but the incidence based on insured population was the highest for those under 20 years old. About 96% of the cases involved finger amputation, and 85% of all amputations were related to common powered machines. The average annual incidence of disability claims due to occupational amputation of upper extremities was 12.5 per 100,000 workers. Claims were most prevalent among manufacturing workers and male workers. The male to female risk ratios ranged from 2.62 for manufacturing workers to 9.05 for transport, storage and communication workers by the Poisson regression analysis. Conclusions Young male manufacturing workers were at high risk of occupational amputation of upper extremities in Taiwan. These results provide an epidemiological base for developing a prevention strategy. Am. J. Ind. Med. 46:649–655, 2004. © 2004 Wiley‐Liss, Inc.